Queer popular culture : literature, media, film, and television - Peele, Thomas (Palgrave Macmillan, 2007)
Queer Popular Culture is an exciting new collection that brings together work from several disciplines that address queer representation in multiple contexts. The articles cover many aspects of contemporary U.S. and international queer culture, including the rise of the queer cowboy, the emergence of lesbian chic, and the expansion of representations of blackness, and work on queer, Taiwanese, online communities. Other essays address queer representations from soap operas to gangster films. The book also includes a pedagogical section that addresses the use of queer concepts in the classroom.